Analysis of Barriers to the Implementation of Electronic Medical Records in the Outpatient Clinic of Gunung Maria Hospital, Tomohon - Angelina Goni; Junita Maja Pertiwi; Windy Wariki (Pancasakti Journal Of Public Health Science And Research, 2025)
The implementation of EMR is expected to improve the quality of healthcare services by facilitating faster access to patient data, reducing recording errors, and enhancing coordination among medical personnel. However, various challenges have been identified in practice, which hinder the system’s effectiveness. This study aims to analyze the barriers to EMR implementation in the Outpatient Clinic of Gunung Maria Hospital, Tomohon. A qualitative approach was employed, using in-depth interviews with informants directly involved in the EMR implementation process. The findings reveal that the barriers arise from multiple aspects. From the human resources perspective, additional time and training are needed to enable staff to adapt to the new system. In terms of technological infrastructure, unstable network connectivity and the limited availability of hardware, such as computers and printers in certain service units, hamper the data input process. Regarding software, the existing system does not fully meet the hospital’s operational needs. Procedurally, insufficient dissemination of the standard operating procedures (SOPs) has resulted in some staff not fully understanding the system’s workflow. Furthermore, the evaluation aspect remains problematic due to the absence of a fully functioning monitoring mechanism. External disturbances, such as power outages, have also contributed to service delays by disrupting the electronic documentation process. In conclusion, the EMR implementation at the outpatient clinic still faces various technical and non-technical challenges. Therefore, improvements and strengthening efforts across multiple aspects are required to ensure that the EMR system can operate more effectively and efficiently in supporting the enhancement of healthcare service quality.